A report of perfusion staffing survey: decision factors that influence staffing of perfusion teams. - Conliffe JA; Riley JB; Clutter J; Wolf K; Murtha S; Conliffe, Jacqueline A; Riley, Jeffrey B; Clutter, Jill; Wolf, Kay; Murtha, Sean (Journal of Extra-Corporeal Technology, 2007)
Health care organizations are becoming increasingly aware of the issues surrounding safe staffing because it affects all of us: the patient, public, profession, policy makers, and employers. The conduct of perfusion has been researched, but environmental factors surrounding perfusion have not. The intent of this study was to identify the current perfusion staff to case ratio, the decision factors used to make staffing decisions, and the relative importance of the factors to staff requirements. A survey instrument was constructed. The questionnaire contained four sections: Hospital Information, Perfusionist Information, Staffing Information, and Additional Feedback. Questionnaires were electronically mailed to American Society of Extracorporeal Society (AmSECT) members who were registered on Perflist. Response rate was monitored, and a follow-up survey was sent. Unfortunately, respondents were not compared statistically with the population on like characteristics, because AmSECT does not currently have information regarding the characteristics of their PerfList members. The staff to perfusion case ratio for 2006 was 120 +/- 46 (SD) cases. The top three factors used by perfusionists to determine the number of staff to hire were the number of heart cases, on-call requirements, and the number of operating rooms. The reported use and importance of the decision factors did not differ significantly when reported by chief perfusionists, clinical perfusionists, or those who reported being involved in staffing. On-call requirements were reported to be used significantly more by chief perfusionists and by high activity perfusion teams when determining the number of staff to hire. Small hospitals tended to use staff experience, medium-sized hospitals reported using the number of operating rooms more often, and larger hospitals used the number of hospitals covered to determine staff requirements. Staffing a perfusion team is a difficult task, and many factors need to be considered. This survey provided a description of the current managerial staffing environment and practice. Further research surrounding the application of these factors to staff scheduling is needed.